![x=(d-c)/(a-b)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mcjpf46islwe1hfe983f6bja4xcthrrn8e.png)
Explanation:
Step 1 - Given data:
ax + c = bx + d,
where a ≠ b and c ≠ d
Step 2 - To find:
x expressed in terms of a, b, c and d.
Step 3 - Solution:
The equation is ax + c = bx + d
⇒ ax – bx + c = d
Arrange x variables on one side, then the equation becomes
⇒ ax – bx = d – c
Take x term as a common factor, then the value becomes
⇒ (a – b)x = d – c
x expressed in terms of a, b, c and d is
![x=(d-c)/(a-b)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mcjpf46islwe1hfe983f6bja4xcthrrn8e.png)